Exceptional lines and higher-order exceptional points enabled by uniform loss - Fanghu Feng; Neng Wang; Guo Ping Wang (Scientific Reports)
Abstract This study theoretically investigates the realization of exceptional points (EPs) in space-time invariant Lorentz dispersive media with uniform loss, which contrasts sharply with conventional approaches that rely on spatial or temporal differential losses. Using the derived full and reduced Hamiltonians, we reveal that uniform loss in Lorentz dispersive media not only introduces attenuation to the eigenmodes of the lossless medium but also enables two distinct types of non-Hermitian couplings: reciprocal and non-reciprocal. Both coupling mechanisms independently contribute to the emergence of EPs. The EPs manifest as exceptional lines (ELs) in the parameter space, and a fourth-order EP (EP4) is formed when three ELs intersect at a single point. Remarkably, at the EP4, all eigenmodes exhibit maximum optical chirality density, presenting potential applications such as chiral sorting. Our findings provide valuable insights into the mechanisms underpinning the formation of EPs.